Molecular Catalysis in “Green” Hydrogen Production - Zaccaria, Francesco; Menendez Rodriguez, Gabriel; Rocchigiani, Luca; Macchioni, Alceo (Frontiers in Catalysis, 2022)
Molecular hydrogen (H2) is considered an ideal energy vector and a clean fuel, due to its zero-carbon combustion. Nevertheless, despite hydrogen is the most and one of the most abundant elements in the universe and in earth crust, respectively, it is always combined with other elements in our planet and never appears in its elemental state. This means that H2 must be produced through, almost always, endergonic processes, whose sustainability depend not only on the starting material but also on the source of energy necessary for these processes to occur. Colors have been assigned to identify the level of sustainability of H2 production with the green one indicating H2 produced by water using a renewable source of energy, preferably the sunlight. Redox water splitting (WS) into H2 (hydrogen evolution reaction, HER) and O2 (oxygen evolution reaction, OER) is, nevertheless, an extremely difficult process not only from the thermodynamic but also from the kinetic point of view. Relevant kinetic barriers are present in both sides of the redox process, especially in OER. For this reason, performing WS in an efficient manner requires the development of active and robust catalysts capable of offering alternative reaction pathways to WS, lowering down the unfavorable kinetic barriers and thus maximizing the energy conversion efficiency. Inspiration for developing efficient catalysts for HER and OER has traditionally derived from Nature, who, over the course of many billions of years, according to the evolutionary theory, has assembled two molecular catalytic pools, namely oxygen evolving complex and ferredoxin/ferredoxin NADP+ reductase, which offer viable kinetic pathways to both OER and reduction of NADP+ (the “biological form” of H2). In the reality, after several attempts of mimicking natural catalysts, the efforts of the researchers have been addressed to different molecular systems, which exhibit best performances, unfortunately often based on noble-metal atoms, especially for OER. In this contribution we review the journey of the development of molecular catalysts for both HER and the OER, highlighting selected systems, which have brought us to the current level of knowledge.